Pemenuhan Nafkah Mut’ah, Iddah, Dan Ma?iyah Istri Sebagai Syarat Penjatuhan Talak Dalam Peradilan Agama Di Indonesia - Syaiful Hidayat (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
In the concept of procedural law in Indonesia, when the verdict has been handed down and divorce has been dropped, the husband is obliged to fulfill his ex-wife's livelihood rights, but in reality the problem arises namely the assumption that after the divorce occurs there is no more thing that needs to be done by the husband, including giving a living to his ex-wife and child after the divorce. The law has arranged a solution for that, namely by the process of execution, but because the execution costs are too expensive compared to the amount of income that is not much, then the community fails to make the request for execution. This is the reason for the policy carried out by the Religious Court